Asuhan Keperawatan Keluarga Pada Tahap Perkembangan Lanjut Usia Dengan Intervensi Pemberian Air Rebusan Daun Sirsak Untuk Menurunkan Kadar Gula Darah Pada Ny. R. Di Kampung Bayur Rt 003/ 004 Peruk Jaya Kota Tangerang - Evi Novita; Alfika Safitri; Rina Puspita Sari; Muhammad Hasan Basri (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Diabetes mellitus is a health problem characterized by an increase in blood glucose levels that has a systemic impact. Diabetes mellitus is a family health problem because its prevalence continues to increase and causes high mortality. The family as a subsystem that is the goal of public health care has a duty to maintain the health of its members, including the management of diabetes mellitus in the family. The purpose of writing is to provide an overview of providing family nursing care with the intervention of giving soursop leaf boiled water to lower blood glucose. The method used with the family nursing care process which consists of assessment, nursing diagnosis, intervention, implementation, and evaluation. The results show that family nursing problems that arise are ineffective family health management, the risk of unstable blood glucose levels, and sleep pattern disturbances. The implementation results show that giving soursop leaf boiled water can reduce blood glucose levels in people with diabetes mellitus from 210 mg/dL before the intervention to 180 mg/dL after three days of giving soursop leaf boiled water. Suggestion nurses can facilitate families to provide soursop leaf decoction water therapy to lower blood sugar levels in people with diabetes mellitus.